2007
DOI: 10.1038/nm1651
|View full text |Cite
|
Sign up to set email alerts
|

Human TH17 lymphocytes promote blood-brain barrier disruption and central nervous system inflammation

Abstract: T(H)17 lymphocytes appear to be essential in the pathogenesis of numerous inflammatory diseases. We demonstrate here the expression of IL-17 and IL-22 receptors on blood-brain barrier endothelial cells (BBB-ECs) in multiple sclerosis lesions, and show that IL-17 and IL-22 disrupt BBB tight junctions in vitro and in vivo. Furthermore, T(H)17 lymphocytes transmigrate efficiently across BBB-ECs, highly express granzyme B, kill human neurons and promote central nervous system inflammation through CD4+ lymphocyte r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
1,162
6
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 1,489 publications
(1,218 citation statements)
references
References 14 publications
37
1,162
6
13
Order By: Relevance
“…There is scant information on a conceivable linkage between obesity and multiple sclerosis, but one study showed reduced disease deterioration in patients on low fat compared with high fat diet [17]. Although EAE is not an ideal model for MS, data presented here suggest that this association is worth investigating, in particular, since a role for Th17 effectors in the penetration of the blood-brain barrier as well as neuronal pathology has been reported [18].…”
Section: Dio Exacerbates Eaementioning
confidence: 74%
“…There is scant information on a conceivable linkage between obesity and multiple sclerosis, but one study showed reduced disease deterioration in patients on low fat compared with high fat diet [17]. Although EAE is not an ideal model for MS, data presented here suggest that this association is worth investigating, in particular, since a role for Th17 effectors in the penetration of the blood-brain barrier as well as neuronal pathology has been reported [18].…”
Section: Dio Exacerbates Eaementioning
confidence: 74%
“…BBB-EC grown in primary cultures were used to generate an in vitro model of the human BBB, as previously reported [46,50,51]. On day 0, BBB-EC were plated on gelatin-coated 3 mm pore size Boyden chambers (Collaborative Biomedical Products, Bedford, MA, USA) at a density of 2 Â 10 4 cells per well in EC Freshly purified human CD4 + T lymphocytes (10 6 cells) were then added to the upper chamber and allowed to migrate for 24 h across BBB-EC either untreated or pre-activated for 24 h with 500 U/mL IFN-b.…”
Section: Transmigration Assaysmentioning
confidence: 99%
“…The transport of different subsets of cytotoxic T lymphocytes from the blood to the brain and spinal cord is critical for lymphocytic infiltration of the CNS, which in turn results in neuronal death. Th17 lymphocytes, which secrete interleukin-17, are considered to play an important role in neuronal death (Stockinger et al, 2007), and Th17 cells have recently been shown to penetrate the BBB (Kebir et al, 2007). The BBB mechanisms that mediate transport of different subsets of T cells into the CNS represent potentially important therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%